New perspectives on computer concepts 2014, brief - Parsons, June Jamrich; Oja, Dan
Designed to get you up-to-speed on essential computer literacy skills, this title provides technical and practical information relevant to everyday life. It incorporates significant technology trends that affect computing and everyday life